2013
DOI: 10.1038/modpathol.2013.101
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC2, MUC5AC, MUC5B, and MUC6 mucins in colorectal cancers and their association with the CpG island methylator phenotype

Abstract: Mucinous differentiation is associated with both CpG island methylator phenotype and microsatellite instability in colorectal cancer. The mucinous phenotype derives from abundant expression of the colonic goblet cell mucin, MUC2, and de novo expression of gastric foveolar mucin, MUC5AC. We, therefore, investigated the protein expression levels of MUC2 and MUC5AC, as well as MUC5B and MUC6, in molecular subtypes of colorectal cancer. Seven-hundred and twenty-two incident colorectal carcinomas occurring in 702 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
118
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 67 publications
16
118
3
1
Order By: Relevance
“…As ANXA10 is not expressed in the normal colon mucosa, 7,14 the upregulation of ANXA10 indicates that the right and left segments of the large intestine have unique tumorigenetic backgrounds. Consistent with previous observations, 18 we observed that the expression of MUC5AC and MUC6 apomucins was strongly associated with molecular features of the serrated neoplastic pathway, such as BRAF mutation, the CpG island methylator phenotype and microsatellite instability. Moreover, we noted an association between these molecular alterations and ANXA10 positivity.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…As ANXA10 is not expressed in the normal colon mucosa, 7,14 the upregulation of ANXA10 indicates that the right and left segments of the large intestine have unique tumorigenetic backgrounds. Consistent with previous observations, 18 we observed that the expression of MUC5AC and MUC6 apomucins was strongly associated with molecular features of the serrated neoplastic pathway, such as BRAF mutation, the CpG island methylator phenotype and microsatellite instability. Moreover, we noted an association between these molecular alterations and ANXA10 positivity.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequent studies have confirmed the simultaneous activation of gastric mucins in serrated neoplasms and associated invasive carcinomas. [16][17][18] Aberrant gastric metaplasia was evident based on an inverse association The results indicated that ANXA10 was the most important partition factor. First split was created by the presence of ANXA10 expression and successfully separated the majority of subgroups 3 and 4 colorectal carcinomas from subgroups 1 and 2.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…All cases were thoroughly investigated for the following histological features: neuroendocrine cytologic subtype (small and large cell), type of the exocrine component (adenomas, adenocarcinomas, squamous cell carcinomas), vascular and perineural invasion, presence of necrosis, mitotic count per ten HPF, level of gut wall invasion or infiltration of peripancreatic tissues, and presence of metastases in local lymph nodes. Intra and peritumoral lymphoid infiltration was evaluated using H&E stained sections and CD3 immunostaining and following the criteria proposed by Walsh et al (2013): peritumoral lymphocytes infiltration was defined as a mantle or cap of lymphoid cells at the deepest point of direct spread. We also counted the number of lymphocytes in three different areas at !40 magnification at this level.…”
Section: Morphological and Immunohistochemical Studymentioning
confidence: 99%